2020
DOI: 10.1128/jcm.01230-20
|View full text |Cite
|
Sign up to set email alerts
|

American Society for Microbiology Provides 2020 Guidelines for Detection and Identification of Group B Streptococcus

Abstract: Maternal colonization with Group B Streptococcus (GBS) is a primary risk factor for early-onset disease (EOD) GBS infection in infants and intrapartum prophylaxis reduces neonatal infection.…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 9 publications
0
66
0
7
Order By: Relevance
“…RCOG recommend cephalosporin use in mild penicillin allergy, and vancomycin in severe penicillin allergy [9]. ACOG advice differs slightly from this in the management of severe penicillin allergy; they recommend clindamycin, but only if the GBS isolate is known to be susceptible to clindamycin; otherwise, vancomycin is recommended [13]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCOG recommend cephalosporin use in mild penicillin allergy, and vancomycin in severe penicillin allergy [9]. ACOG advice differs slightly from this in the management of severe penicillin allergy; they recommend clindamycin, but only if the GBS isolate is known to be susceptible to clindamycin; otherwise, vancomycin is recommended [13]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A review of GBS policies worldwide showed that the majority (63%) of countries surveyed had an IAP policy, over half (58%) used microbiological screening, and many (42%) used a clinical risk-factor-based policy [11]. In the USA, the Center for Disease Control (CDC), American College of Obstetricians and Gynaecologists (ACOG) and American Society for Microbiology (ASM) recommend universal antenatal screening, comprising culture testing for GBS at 36-38 weeks and providing IAP for those who are positive, in addition to the use of IAP because of GBS bacteriuria in the current pregnancy or a history of previous GBS-infected neonate [8,12,13]. This approach is also recommended by the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) [14] and has been implemented by several European countries, including France [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal samples were processed for the detection of GBS according to the American Society for Microbiology's guidelines (13). Brie y, vaginal samples were inoculated in 1-2 mL of Todd-Hewitt broth supplemented with colistin 10 µg/mL and nalidixic acid 15 µg/ mL and incubator at 35°C for 18-24h.…”
Section: Identi Cation and Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Her publication and presentation record has focused on tuberculosis, fungal diseases, public health microbiology, emerging infectious diseases, and detection of antimicrobial resistance. She has participated in publication of intersociety guidance documents ( 2 , 3 ), coauthored several chapters of the Clinical Microbiology Procedures Handbook ( 4 – 6 ), and contributed to initial characterization of Staphylococcus aureus isolates in the United States with decreased susceptibility to vancomycin ( 8 ). Dr. Robinson-Dunn has been awarded fellowships by both the Infectious Diseases Society of America and the American Academy of Microbiology and was bestowed with the Research, Epidemiology and Laboratory Public Health Practice Program Award from the Centers for Disease Control and Prevention in 2003.…”
Section: Editorialmentioning
confidence: 99%